PENINGKATAN KETERAMPILAN MANAJEMEN USAHA BAGI MAHASISWA KEPERAWATAN MELALUI PELATIHAN KEWIRAUSAHAAN - Siti Maryati (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
Background The problems experienced as a manager of health education that the number of nursing graduates from vocational education to master reaches 24000-25000 people per year. The low absorption of graduate nursing education and the limited employment opportunities for nurses in government institutions. It would need to nurse provided the ability / skill other in order to open up business opportunities independently or collaborating entrepreneur's ability to do since I was a student and when it's completed education. How to Troubleshooting, efforts to equip abilities / skills of nurses do entrepreneurs by giving lectures on entrepreneurship and giving Entrepreneurship Training. This activity aims to provide skills of nurses in the management of care services in the "Clinic Home Care" or perform other entrepreneurs.The target are nursing students and alumnis of nursing college of Akes Husada Yogyakarta with participant 20 people tenant, 16 people from nursing students and 4 from alumnis Method of training is done through lectures, demonstrations, visits and internships. Target outcomes is the establishment of new entrepreneurial activities in the field of goods and services. The results obtained in 2015 (1) Support from Technological Knowledge and Skill for Entrepreneurship has implemented by nursing college of Akes Karya Husada and produce 6 students as new entrepreneurs who run business in goods and services, (2) Realization of Entrepreneurial Incubation Technological Knowledge and Skill for Entrepreneurship form Clinic Home Care as a center of entrepreneurship in the development of an entrepreneurial culture (3) Realization of entrepreneurship capacity building system for students in Technological Knowledge and Skill for Entrepreneurship under the body of Research and Community Service Akes Karya Husada Yogyakarta. Conclusion Technological Knowledge and Skill for Entrepreneurship Akes Karya Husada Yogyakarta fiscal year 2015 resulted in 6 new students as entrepreneurs who conduct business in a variety of business products such as home care services as well as a variety of other business products,Keywords: health education, nursing, training.